Implementation of Core Values "BerAKHLAK" In Improving Professionalism and Performance of State Civil Apparatus - Brumadyadisty, Garry (Journal of Business Management and Economic Development, 2025)
The State Civil Apparatus (ASN) in Indonesia is undergoing a transformative shift with the implementation of the BerAKHLAK core values—Berkualitas (Quality), Akuntabel (Accountability), Harmonis (Harmonious), Loyal, Adaptif (Adaptive), and Kolaboratif (Collaborative). Launched in 2021, BerAKHLAK aims to enhance professionalism, accountability, and service quality in public administration. However, research on its localized implementation in complex administrative settings like East Java remains limited. This study evaluates the implementation and impact of BerAKHLAK on the professionalism and performance of ASN in East Java, with a focus on internalization processes, challenges, and outcomes. The research employed a qualitative case study approach, gathering data from 30 diverse participants, including ASN personnel, supervisors, and service recipients. Data collection methods included semi-structured interviews, focus group discussions, and document reviews. Thematic analysis was conducted within the framework of organizational culture theory and performance management models. The study identified structured implementation strategies such as monthly workshops, mentoring programs, and performance dashboards. Leadership played a critical role in fostering a values-driven culture. Key challenges included resistance from older employees, inconsistent leadership commitment, and limited digital infrastructure. Despite these barriers, BerAKHLAK significantly improved service quality, interdepartmental collaboration, and public satisfaction. The findings highlight the transformative potential of BerAKHLAK in fostering ethical governance and professionalism. However, strategic leadership, adaptive training, and technological investment are necessary to address challenges and sustain its impact.